Raising the Stakes: Consequential Learning Practices in College Communication Courses. - Stevenson, Robert; Duncan, Graham (Experiential Learning and Teaching in Higher Education, 2025)
While we agree that it is important for students to have class projects and assignments that allow them to build firsthand experiences in scenarios they will face again in their workplaces and the world, we also believe that it is important for educators to craft experiences that challenge students of communication to make decisions resulting in consequences (positive or negative) beyond their grade. This paper will share our experiences teaching two college-level communications courses, both of which include projects that require communication students to build authentic, usable communications that have implications beyond the course.